Al-Maqrizi Views on Economic Inflation - Hasna Maliha; Aam Slamet Rusydiana (Islamic Economics and History, 2022)
One of the important problems facing the world economy until now is the problem of inflation. In simple terms, inflation means an increase in the price of goods from its usual state. In fact, long before the economic thinking of experts such as Friedman, Fisher, Keynes, and other world economists regarding inflation and other monetary matters, the Islamic world had earlier figures who were concerned in this field. Taqiyuddin Abul Abbas Al-Husaini from Maqarizah, Cairo. Or better known as Al-Maqrizi. Maqrizi said in several parts of his book that inflation is generally divided into two, namely Natural Inflation and Human Error Inflation. This paper will try to compare some of his thoughts –particularly the problem of inflation- with conventional positivistic opinions and concepts in similar fields.